Strategi Pengembangan Ekonomi Kreatif melalui Inovasi Keripik Kelapa: Studi Kasus Desa Blang Cut - Nufus, Hayatun; Nabila, Alya Maulida; Wahyuni, Ayu; Hilwa, Cut; Febriana, Nana; Nirwana, Iqrya; Agustina, Yeni; Miftahudin, Miftahudin; Raihan, Muhammad Ade; Pratiwi, Salmi Indah; Hasami, M (Ibrah : Jurnal Pengabdian Kepada Masyarakat, 2024)
This service-based research aims to empower the community of Blang Cut Village, Meurah Mulia District, North Aceh Regency, through training in coconut processing into coconut chips. A Participatory Action Research (PAR) approach was applied to actively involve the community in all stages of the activity, which included observation, planning, experimentation, implementation, and evaluation and reflection. The research was conducted in November 2023, with a method involving cycles of planning, action, observation, and reflection according to the action research framework. Data collection techniques included semi-structured interviews, participatory observation, and participant satisfaction surveys, which were analyzed using qualitative, quantitative, and SWOT approaches. The results showed an increase in participants' skills and confidence in processing coconut independently, with 85% of participants feeling capable of producing coconut chips after the training. The satisfaction survey noted that 90% of participants were satisfied with the learning-by-doing method applied. From an economic perspective, there was an increase in community awareness of the potential added value of the product, which was previously only sold as raw coconut at Rp3,000 per grain, to coconut chips at Rp10,000 per pack. Social impacts include the formation of joint business groups and increased community solidarity. The implications of this research include strengthening the local resource-based creative economy, particularly in the development of Micro, Small, and Medium Enterprises (MSMEs). The program encourages village economic sustainability through collaboration with the government and local MSMEs, as well as the potential for developing other innovative products. With follow-up in the form of continuous assistance, Blang Cut Village can become the center of the coconut-based creative economy in the region.